Triphenylphosphine gold(I) derivatives promote antiviral effects against the Chikungunya virus - Aires, Rochanna L.; Santos, Igor A.; Fontes, Josielle; Bergamini, Fernando R. G.; Jardim, Ana Carolina G. [UNESP]; Abbehausen, Camilla (Oxford Univ Press, 2022)
Herein a systematic series of four [AuLL'](n+) n = 0, +1 complexes, where L = 1,3-bis(mesityl)imidazole-2-ylidene (IMes), or triphenylphosphine (PPh3), and L' = chloride, or 4-dimethylaminopyridine (DMAP), had their in vitro antiviral activity assessed against Chikungunya virus (CHIKV). The PPh3 derivatives inhibited viral replication by 99%, whereas the IMes derivatives about 50%. The lipophilicity of the PPh3 derivatives is higher than the IMes-bearing compounds, which can be related to their more prominent antiviral activities. The dissociation of DMAP is faster than chloride in solution for both IMes and PPh3 derivatives; however, it does not significantly affect their in vitro activities, showing a higher dependence on the nature of L rather than L' towards their antiviral effects. All complexes bind to N-acetyl-L-cysteine, with the Ph3P-bearing complexes coordinating at a faster rate to this amino acid. The binding constants to bovine serum albumin are in the order of 10(4), slightly higher for the DMAP complexes in both PPh3 and IMes derivatives. Mechanistic investigations of the PPh3 complexes showed a ubiquitous protective effect of the compounds in the pretreatment, early stages, and post-entry assays. The most significant inhibition was observed in post-entry activity, in which the complexes blocked viral replication in 99%, followed by up to 95% inhibition of the early stages of infection. Pretreatment assays showed a 92% and 80% replication decrease for the chloride and DMAP derivatives, respectively. dsRNA binding assays showed a significant interaction of the compounds with dsRNA, an essential biomolecule to viral replication.
Keywords: Chikungunya; Gold; Metallodrugs; Antivirals